Unmasking Cost Stickiness in The Era of Digital Transformation - Phan Meliana Wijaya; Mitha Dwi Restuti (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2026)
This study examines how digital transformation shapes cost behavior in Indonesia’s consumer non-cyclical sector. Analyzing 326 firm-year observations (2021–2023) using Generalized Least Squares, the findings reveal cost anti-stickiness: firms cut expenses more aggressively during revenue declines. Digital transformation, however, increases cost stickiness due to high upfront investment, adjustment barriers, and strategic optimism, while labor productivity and working capital improve cost flexibility. The results highlight a paradox: digitalization constrains short-term flexibility but reinforces long-term resilience. Firms must therefore balance technology investments with operational agility to build adaptive cost structures in volatile environments.